Una historia comparada del cine latinoamericano - Schroeder Rodríguez, Paul A. (Nexos y Diferencias. Estudios de la Cultura de América Latina, 2020)
This book traces a comparative history of the national cinemas of Latin America, in ten chapters that cover the main cinematographic periods of the region, among them silent cinema, studio cinema, neorealism, auteur cinema, the New Latin American Cinema and contemporary cinema. Contains the translation of the English edition "Latin American Cinema: A Comparative History" (University of California Press, 2016). The edition presented also includes a new section on memory and an analysis of the film "Roma" by Alfonso Cuarón, added to the final chapter.